2008
DOI: 10.1002/jid.1501
|View full text |Cite
|
Sign up to set email alerts
|

Exports and economic growth: The case of South Africa

Abstract: Economic policy has always accorded an important role to export production in the overall growth process in South Africa. Recent policy proposals once again reaffirm this commitment. This paper attempts to ascertain whether the emphasis on export production is justified. Using modern econometric techniques within a multivariate framework, the results show that there is uni-directional Granger-causality running from exports to economic growth in South Africa. In addition, the gross domestic product (GDP) accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…The study revealed that exports Granger-cause GDP, and suggested that the export-led growth strategy through various incentives has a positive influence on growth. Rangasamy (2008) examined the exports and economic growth relationship for South Africa. The study provided an evidence of unidirectional Granger causality runs from exports to economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that exports Granger-cause GDP, and suggested that the export-led growth strategy through various incentives has a positive influence on growth. Rangasamy (2008) examined the exports and economic growth relationship for South Africa. The study provided an evidence of unidirectional Granger causality runs from exports to economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Avocado, apple, mango and orange production in South Africa over the decade has shown good growth trends. In South Africa recently, empirical studies carried out (Dlamini and Fraser, 2010;Rangasamy, 2009;Pearson et al, 2010) to appraise the impact of export growth in comparison to economic growth, comparatively yet little has been done to analyse the impact of a single or few produce within the agricultural sector. The issue of how South Africa's agricultural sector can greatly contribute to economic growth is one of the fundamental economic questions which need proper considerations.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars, digging the exports, have come up with interesting conclusions. For example, Abu-qarn and Abu-bader (2004), Herzer et al (2006) and Rangasamy (2009).…”
Section: Significance and Objectivesmentioning
confidence: 99%